La «tyrannie» de la mémoire - Dosse, François (Tripodos. Facultat de Comunicació i Relacions Internacionals Blanquerna-URL, 2009)
We are experiencing today everything related to memory, which is perhaps the sign of a new regime of historicity privileging the present and a symptom of the crisis of the future. While one should maintain a critical regard, that of the historian on the memorial legacy, one must also be careful not to challenge the memorial dimension which has greatly enriched the historical discourse. The problem of the places of memory permits this double movement of appropriation and of critical distance which augurs a new way of writing history, starting from its footprints. Key words: Regime of historicity. places of memory, appropriation, critical distance, footprints.